Mirror as Prism: Reimagining Reflexive Dispute Resolution Practice in a Globalized World - Kenneth H. Fox (Washington University Journal of Law & Policy, 2014)
As cooperative private international dispute resolution practices become increasingly common, it is tempting for conflict practitioners to assume that the human relations insights, skills, and practices that worked well for them at home will be equally effective (and appropriate) in an international, cross-cultural environment. However, exporting the ways we understand and interact with others in conflict from a domestic environment into new and different legal, political, economic, cultural, and social environments can be problematic. As a result, attending to the human dimension of conflict and interaction should be a central part of global negotiation and dispute resolution practice. That is the focus of this Essay. This Essay focuses on two dimensions of reflective and reflexive practice. Professor Fox discusses the nature of reflection-on-action and reflection-in-action from a modernist (“reflective”) and postmodern (“reflexive”) perspective. These modern and postmodern concepts of reflective and reflexive practice parallel a growing trend in the conflict literature from a “modernist” to a postmodern or “social constructionist” orientation to understanding conflict itself. Professor Fox then examines how engaging with practice reflexively reveals additional dimensions of awareness about ourselves, other parties, and the conflict context. Professor Fox then brings together the elements of reflective and reflexive practice to articulate a more holistic conception of “awareness” that can help conflict practitioners more purposefully learn from past experience and develop greater awareness as conflict interactions unfold.
Keywords: international commercial arbitration; cross-cultural dispute resolution; cultural awareness; social awareness; reflective conflict interaction; reflexive conflict interaction; reflexive-on-action; reflexive-in-action; awareness of self; awareness of other; awareness of context